Isolasi, Seleksi dan Karakterisasi Bakteri Mannolitik yang berasal dari Serasah Tanaman Sawit - Apriani, Ike (BIOILMI, 2015)
Mananase enzyme used to hydrolyze manan in producing simple sugars, such as mannose and monooligosakarida which will be utilized in the industry. Mananase enzymes produced by microbes more attractive to industry because it is more economical, higher productivity and amore controlled production conditions. Mannolitic bacteria isolated from soil containing palm litter. Isolation is done by using selective media locus bean gum. The result showed 6 bacterial isolates that have the ability mannolitic. Isolate 6 has the highest mannolitic index of 0.85. Isolates 6 were characterized morphologically, showed that this isolate motile, cocci, and gram-negative. Physiological characterization showed that this isolate utilize peptone as a source of energy that is supported by VP and H2S test results were positive.